FERMENTATION OPTIMIZATION FOR PRODUCTION OF POLYHYDROXYBUTYRATE (PHB) BY NEWLY ISOLATED AZOTOBACTER VINELANDII KDP - M. UMA MAHESWARI; K. DHANDAYUTHAPANI (International Journal of Pharma and Bio Sciences, 2013)
Producing the biodegradable plastic is the most important processes nowadays because to overcome the recent issues concerning the global environment and solid waste management. The optimum conditions for PHB production are more important to enhance the production by microorganism. In the present investigation newly isolated Azotobacter vinelandii KDP culture conditions were optimized to produce PHB. The optimum pH and temperature of media for biomass and PHB production by A. vinelandii KDP was 7.0 and 350C respectively. Maximum biomass (2.67g/l) and PBH (2.18g/l) production obtained at 5g/l sucrose contained media. 2.0 mM/l NH4Cl was the best concentration for maximum yield of PHB (1.28g/l). Optimum concentration of trace metal selenium for maximum yield of biomass and PHB production was 80µg/l. Under this optimum condition A. vinelandii produced two fold PHB